Risk Disclosure and Risk Management in Well performed and Under performed Companies in Oil and Gas Industry - wang, fei (2007)
This dissertation selects twenty companies in oil and gas industry randomly. By comparing their increased percentages in share prices in the period between 2002 and 2006, the companies are categorised into two groups: well performed and under performed companies.